Pesan Dakwah dalam Channel Youtube YtCrash Islam - Agustian, Robby (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2022)
This study aims to explore and understand how to categorize informative, persuasive, and recreational da'wah messages contained in YtCrash Islam's content. The research method used in this research is descriptive qualitative with data collection techniques how to watch and observe, record, process data by coding, observation, and documentation on the object of research. The results of this study refer to how the form of the da'wah message is conveyed in YtCrash Islam's contents. In the YtCrash Islam channel, 42 da'wah messages were found consisting of informative, persuasive, and recreational da'wah messages. Informative da'wah messages contain light information news offerings including messages of aqidah, shari'ah, and morals. Persuasive da'wah messages contain the value of an invitation to practice Islamic law such as worship, zakat, and other practices. Recreational da'wah messages that contain inspirational stories and stories. Keywords : Da'wah; Message of Da'wah; Social Media; Youtube